Chain rule

  • Thread starter cowgiljl
  • Start date
  • #1
cowgiljl
63
1
g(x) = (4+csc^2(3x))^2

this is what i got
1/2(4+csc^2(3x))^-1/2 * d/dx (4+csc^2(3x)

g'(x) = 1/2(4+csc(3x))^-1/2 (1+cot3)
did i go about this correct to get the answer or did i mess it up at the diretive part?

joe
 

Answers and Replies

  • #2
motai
358
2
Is the question g(x) = (4+csc^2(3x))^2 or g(x) = (4+csc^2(3x))^1/2?

This makes a difference when applying the chain rule.
 
  • #3
cowgiljl
63
1
g(x) = (4+csc^2(3x))^1/2?

it is this one it was orginally the squrt of 4+csc^2(3x) i just attempted to simplify it
 
  • #4
motai
358
2
Yeah, from your work g(x)=(4+csc^2(3x))^2 should be

g(x)=2(4+csc^2(3x))^1 * d/dx (4+csc^2(3x)) instead of
g(x)=1/2(4+csc^2(3x))^-1/2 * d/dx (4+csc^2(3x))

otherwise that last one would have corresponded an original equation written as g(x)=(4+csc^2(3x))^1/2
 

Suggested for: Chain rule

  • Last Post
Replies
2
Views
309
Replies
6
Views
496
  • Last Post
Replies
6
Views
767
Replies
5
Views
112
  • Last Post
Replies
5
Views
686
  • Last Post
Replies
2
Views
486
  • Last Post
Replies
1
Views
686
  • Last Post
Replies
2
Views
891
  • Last Post
Replies
4
Views
764
  • Last Post
Replies
2
Views
717
Top